Impact of ESG Risk Ratings on Stock Prices: Evidence from ESG Leaders Index Companies (2020–2023) - Celvin Yusra; Susi Sarumpaet; Agrianti Komalasari; Sari Indah Oktanti Sembiring (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study investigates the impact of Environmental, Social, and Governance (ESG) Risk Ratings on stock prices of companies listed in the ESG Leaders Index on the Indonesia Stock Exchange during the period 2020–2023. Using the Ohlson (1995) valuation model as the theoretical framework, the research examines the value relevance of financial information—proxied by Book Value per Share (BVPS) and Earnings per Share (EPS)—and non-financial information in the form of ESG risk ratings. The study employs purposive sampling, resulting in an unbalanced panel dataset of 120 firm-year observations. Panel regression analysis with the Random Effect Model (REM) is applied, supported by classical assumption tests and sensitivity analysis. The findings reveal that BVPS has a positive and significant effect on stock prices, highlighting its role as a stable and value-relevant measure for investors. By contrast, EPS shows a positive but insignificant relationship, confirming the declining relevance of earnings in the Indonesian market. Moreover, ESG Risk Ratings exhibit a negative but statistically insignificant effect, suggesting that while firms with higher ESG risks tend to be valued lower, sustainability considerations are not yet consistently incorporated into equity valuation by Indonesian investors. These results imply that financial fundamentals, particularly BVPS, remain the dominant factor in stock price determination, whereas ESG information has not yet achieved value relevance in the Indonesian context. The study underscores the need for stronger regulatory enforcement, standardized ESG disclosure, and greater investor awareness to enhance the integration of sustainability risks into capital market decision-making.